(untitled) (Agora for Physical Education and Sport, 2021)
The aim of this paper was to know future primary school teachers’ opinion about the PE they lived when they were students, and what could be their social function at school to face new educational challenges. According to the phenomenological method, we analyzed the content of some short stories written by 233 students of the Faculty of Education (University of Barcelona) about their memories in the PE lessons at primary school. Results indicated that sport continuous being the most popular content, although this doesn’t mean that it provides useful learning outcomes to all students. Future primary school teachers also think that an alternative approach to PE is required to face the new educational challenges of the digital era.